Digital Transformation in Marriage Administration: Analysis of The Implementation of the ELSIMIL Application in Marriage Registration - Syatta, Indy Mafiiqo (International Journal of Law Dynamics Review, 2024)
The development of information technology has changed many aspects of life, including government administration, for example, the application "elektronik siap nikah dan hamil" (ELSIMIL) as a marriage registration process at the Office of Religious Affairs (KUA), which is used to simplify the marriage administration process. This article aims to understand how this application works and identify the efficiency and accuracy of marriage registration, as well as public response to the use of technology in marriage registration administration. KUA Purworejo, Pasuruan is used as a research location, the research methods include empirical juridical data collection, data processing, and drawing descriptive-analytical conclusions. The findings of this study show that the ELSIMIL certificate as a mandatory requirement for registering as a bride-to-be at KUA has been implemented well. These benefits are in the form of better accessibility and availability of KUA services for the community, both through online services and offline services when people visit the KUA office. It also enhances cooperation among institutions, civil society organizations, or other religious institutions, which automatically helps KUA expand the range of services and resources available to the community. ELSIMIL certificate as a condition for holding a marriage, can treat brides-to-be who have health risks that are not ideal for pregnancy preparation.